Cerebellar connections to the dorsomedial and posterior nuclei of the hypothalamus in the rat - (:unkn) unknown (My University, 2001)
The stimulation or ablation of cerebellar structures has produced a variety of visceral responses, indicating a cerebellar role in visceral functions. Studies using anterograde and retrograde tracing methods have revealed connections between the hypothalamus and cerebellar structures. The aim of this study is to investigate the cerebellar connections of the dorsomedial (DMH) and posterior hypothalamic nuclei using retrograde axonal transport of horseradish peroxidase (HRP). In the present study, micro-injection of HRP restricted within the borders of the DMH showed that the projections of this nucleus are not uniform throughout its extent. The posterior DMH receives projections from the cerebellum, whereas the anterior DMH does not. These projections were from the (greatest to least concentration) lateral (dentate), anterior interposed (emboliform), and medial (fastigial) cerebellar nuclei. In addition, both the anterior and posterior DMH receive projections from various areas of the brainstem which confirms earlier studies and provides detailed descriptions. This study also demonstrates the distribution of labelled neurons to cerebellar and brainstem nuclei following HRP injection into the posterior hypothalamic nucleus. It provides clear evidence for a direct cerebellar nuclei-posterior DMH and cerebellar nuclei-posterior hypothalamic nucleus connections. We suggest that the brainstem reticular nuclei and other connections, such as the solitary, trigeminal and vestibular nuclei, of both DMH and posterior hypothalamus may contribute to the indirect cerebellohypothalamic connections. These observations offer a new perspective on the question of how the cerebellum may influence autonomic activity.
Keywords: Cerebellum; Dorsomedial hypothalamic nucleus; Posterior hypothalamic nucleus